The Effect of Dow Jones Islamic Market World Index, Foreign Exchange, Foreign Investment and Domestic Investment with the Intervening Composite Stock Price Index on the Indonesian Sharia Stock Index - Sofyan Halim (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. The purpose of this research is to know the effect of the DJIMWI, Forex, Foreign Investment, Domestic Investment on the Indonesian Sharia Stock Index (ISSI) with the intervening of JCI in the research period. Through regression analysis, this study concludes that the DJIWMI and the foreign exchange variables have significant positive effect on the JCI. However, the JCI is not significantly affected by the foreign investment but is influenced by domestic investment. Furthermore, it shows that DJIMWI and domestic investment have a significant positive effect on ISSI. The pathway analysis shows that there is a significant effect between the JCI variables on the ISSI. DJIMWI through the JCI has a significant influence on ISSI. Meanwhile, the foreign exchange variable through the JCI has a significant influence on the ISSI variable. On the other hand, the variable of foreign investment through the JCI has no significant effect on ISSI; however, domestic investment through the JCI has a significant influence on ISSI. The limitations of the study are factors outside the research model, which are 25.88% and 53.47% of the dependent variable of JCI and ISSI.Keywords: Dow Jones Islamic Market World Index, Foreign Investment, Domestic Investment, Indonesian Sharia Stock Price Index, Composite Stock Price Index, Foreign Exchange Rate Abstrak. Tujuan dari Penelitian ini untuk mengetahui pengaruh dari variable Dow Jones Islamic Market World Index (DJIMWI), valuta asing, investasi asing, investasi domestik terhadap Indeks Saham Syariah Indonesia dengan intervening variabel IHSG pada periode yang dikaji. Melalui analisis regresi, penelitian ini menyimpulkan bahwa DJIWMI dan valuta asing berpengaruh positif secara signifikan terhadap IHSG. Namun demikian, IHSG tidak terpengaruh secara signifikan oleh investasi asing, tetapi dipengaruhi oleh investasi domestik. Selanjutnya, studi ini menunjukkan bahwa DJIMWI dan investasi domestik berpengaruh positif secara signifikan terhadap ISSI. Hasil uji melalui analisis pathway menunjukkan adanya pengaruh signifikan antara variabel IHSG pada ISSI. DJIMWI dan valuta sing melalui IHSG memiliki pengaruh signifikan terhadap ISSI. Di sisi lain, investasi asing melalui IHSG tidak berpengaruh signifikan terhadap ISSI; namun investasi domestik melalui IHSG memiliki pengaruh signifikan terhadap ISSI. Keterbatasan penelitian ada pada faktor di luar model penelitian sebesar 25,88% dan 53,47% dari variable dependen IHSG dan ISSI.Keywords: Dow Jones Islamic Market World Index, Investasi Asing, Investasi Domestik, Indeks Saham Syariah Indonesian, Indeks Harga Saham Gabungan, Valuta Asing